Morbidity, its Patterns and Associated Factors among School Children Residing in a North Indian City - Sebastian Christian; Manasvi Duggal; Shalini Dehal (International Healthcare Research Journal, 2021)
INTRODUCTION: Children are the pillars of the future of a country shall rest, are no less than a treasure and need to be as healthy as possible. AIM: To assess the health status of school children in various areas of Una city, Himachal Pradesh, India. MATERIALS AND METHOD: The present study was conducted among school children aged 7-18 present on the day of the study. Data collected was cross-sectionally using a pre-validated and pre-tested questionnaire duly standardized prior to commencement of the study. The first section of the questionnaire contained details about the demographic profile, and in the second, the examiners recorded the presence or absence of common childhood diseases, namely pallor, lymphadenopathy (L.N.), Bitot spots, Worm infections, Scabies, Ear discharge, Dental caries and Fluorosis.  Statistical analysis included the Shapiro-wilk test to check for data normalcy, followed by descriptive statistics and Pearson’s correlation. Significance value (p) was kept significant at ≤0.5. RESULTS: Most children belonged to the age group of 12-15 years (42.8%), followed by 7-11 years(34.3%) and 16-18 years(22.9%). Majority of the students were girls (61.5%) and most them belonged to the age group of 12-15 years(41.0%). Disease in any from was observed in 813 (76.2%)  of the children, with the most prevalent disease observed being dental caries (32.3%), followed by fluorosis (20.5%) and pallor (14.3%). Pearson’s correlation revealed a strong, positive association between the disease status and age (0.7) and gender (0.8). CONCLUSION: The results of the present study indicate the need to have various specific programmes to reduce the burden of various diseases, namely dental caries and pallor among school children through efforts of various programmes.